Heterogeneous Catalysts SILP with Phosphotungstic Acid for Oxidative Desulfurization: Effect of Ionic Liquid - Bryzhin, A. A.; Buryak, A. K.; Gantman, Mikhail; Zelikman, V. M.; Shilina, M. I.; Tarkhanova, I. G. (Kinetics and Catalysis, 2020)
Abstract: SILP (supporting ionic liquid phase) catalysts for peroxide thiophene oxidation were obtained on silica gel, they included imidazole cations with sulfonic acid group and phosphotungstate anions. The composition of the active phase and the surface structure of the catalysts are characterized by a set of modern physicochemical methods, including mass spectrometry using the SALDI technique. It was found that the organic cation structure affects the stability of heteropolyanions, decomposition processes in the SILP and the catalytic properties of the samples. SILP catalysts are effective in desulfurization of the diesel fraction and provide fuel with an S content of less than 10 ppm.
CRIS-Team Scopus Importer:2020-10-16
Keywords: diesel desulfurization; hydrogen peroxide; phosphotungstic heteropolyacid; SILP catalysts; thiophene oxidation